The Effect of Using I-STEM Modules on Primary Level Learners’ Critical Thinking: A Case Study in Lebanon - Abou Afach, Sara; Kebbi, Ibrahim (Advances in Social Sciences Research Journal, 2022)
STEM is the acronyms of Sciences Technology Engineering and Mathematics that teachers been using in their classroom since long ago. Recently, the focus is to revamp and bring STEM in classes to build learners’ skills. The purpose of this study is to determine the effect i-STEM program in enhancing learners’ critical thinking skills by applying methods and techniques adopted from one disciplines into another in order to solve an assigned problem relevant to learners’ life. The research methodology for this study followed both paradigm, the qualitative and quantitative. This was needed for a better understanding of the situation due to the lack of studies on this topic. Questionnaire, Project rubric, reflection tool and interview were done to collect data. The relatability and validity of the tools has been ensured. The study has been conducted in one private school in Beirut, Lebanon, on grade 5 learners, N=117. The intervention duration lasted 6 months from January until June. 8-Steps i-STEM thinking process was used in the classroom to facilitate the integration of i-STEM. Results showed a significant improvement of learners’ critical thinking after implementing i-STEM.